Transmission loss of a sound insulating panel made from charged recyclable thermoplastic - Regnard, Jean-Philippe; Panneton, Raymond; Elkoun, Said; Oddo, Rémy (Canadian Acoustics, 2011)
This article aims at investigating the sound insulation property of composites made of recyclable thermoplastic charged with heavy particles. Polyethylene (PE) is the most used thermoplastic polymer worldwide. Behind this generic name lies several types of PE, where linear low density polyethylene (LLDPE) is the most common one. Metal particles are often used to improve the electrical properties of materials. However Young modulus increases too. Subsequently, and in order to reduce composites rigidity, samples microstructure was modified by subjected all composites to a special procedure. Then, Young modulus was again reevaluated. Buoyancy method was used to assess the composites density. In this work, it was shown that the sound insulation properties of a material made of recyclable thermoplastic can be assessed by the rigidity to density ratio, and, enhanced by reducing this ratio.